Images of avengers in Anton Chekhov`s Fatherlessness. The hero in the situation of a revenge - Szymańska, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
The aim of this article is to analyze the images of the two heroes of Chekhov`s early drama – the horse-thief Osip and Sophia Voynitseva, as characters that are similar to Commander, one of the heroes of the Don Juan story. A rtesponse to the Commander in Fatherlessness allows us to interpret Chekhov`s play in an ironic way and contributes to new value of this drama.